Digital Teaching Material Poetry Texts To Improve Middle School Students' Poetry Writing Skills - Yuniati, Umaerah Yuyun; Kusmana, Suherli; Arfiyanti, Riskha (Jurnal Edusci, 2025)
Aim. This research aims to address the issues faced by students who experience a decline in learning ability and motivation and the limited availability of easily accessible learning materials outside the classroom.  Methods. The research method used is research and development.  This research is based on a study of the need for teaching materials for students in the Indonesian language subject at the junior high school level in the Indramayu Regency.  Based on the background and objectives of the research, this study aims to provide an overview of the use of digital learning materials in students' creative writing process.  The research and development method used in this research is based on the ADDIE steps.  Result. The development design is grouped into five development procedures, which include the analysis stage, design stage, development stage, implementation stage, and evaluation stage.  Data collection used interview and observation guidelines, questionnaires for subject matter experts, questionnaires for media and graphics experts, and student response questionnaires. Conclusion. The description of this research suggests that digital teaching materials can facilitate students' creative processes. Implementation. Students can also find alternative problem-solving methods and develop an openness to various experiences with a very high level of flexibility and tolerance towards uncertainty. Making students also have satisfaction with what they do and an attitude of appreciating the work of others.